Perspectiva de um sistema elétrico inteligente em uma cidade brasileira: estudo de caso Búzios - Lago, Renard Lopes Villas Boas do (2019)
In seeking the construction of an intelligent city there is a need to identify the processes that may or may not contribute to its construction and which challenges to overcome, taking into account the aspects of urban life, such as mobility, security, communication systems, sanitation and also for the electrical system. This research is a case study with the purpose of transforming Búzios into an intelligent city, as it is published by the municipal administration. The study aimed to verify if all the projects presented were executed and if the concepts of sustainability, rationality and loss control are being applied. The approach defined for research was qualitative, verifying the facts and seeking to clarify the dynamics of social relations, through a descriptive and exploratory research. During the visit to the city information was collected through interviews and direct observations, among the interviews were qualified 20 residents and collected 202 photographs. Among the projects implemented and in operation are three generators of photovoltaic energy, as for the projects implemented and that presented discontinuity and failures in its operation are the intelligent LED lighting system, the free internet system project, the projects with the systems of generation of aerogenerator energy, power network automation projects and installation projects of smart meters. During the technical visit, it was not possible to identify characteristics or contributions that define the city of Búzios-RJ, as the first intelligent city in Latin America, as little as an intelligent city, once the projects executed show flaws, a small part of the city was contemplated, the population does not have knowledge about the project, lack of continuity and governance. Although the projects listed make sense as components of an intelligent city with an intelligent electric grid, it was not possible to characterize the city as "intelligent" since the projects did not show, in their majority, effectiveness and scope enough to do so. The city can, however, become intelligent by expanding the reach and effectiveness of the projects.